Enhancing the carbon capture capacities of a rigid ultra-microporous MOF through gate-opening at low CO2 pressures assisted by swiveling oxalate pillars. Issue 9 (15th December 2015) - Banerjee, Aparna; Nandi, Shyamapada; Nasa, Parveen; Vaidhyanathan, Ramanathan
Abstract : Up to 40% (@273 K) enhancement in CO2 capacities in a rigid ZnAtzOx framework via 'swivelling' oxalate assisted gate-opening. Abstract : Porosity enhancement assisted by an unusual gate opening has been realized in an exceptionally rigid ultra-microporous framework. The gate-opening has been attributed to the presence of symmetrically positioned Zn–O bonds of the Zn–oxalate units that facilitate subtle swiveling motion resulting in a drastic improvement (42%) in the CO2 capacity without compromising the CO2 /N2 selectivity.